2013
DOI: 10.1111/jgh.12178
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori infection and the effect of its eradication on symptoms of functional dyspepsia in Kashmir, India

Abstract: Background and Aim: Epidemiology of Helicobacter pylori infection has regional variation. Effect of eradication of H. pylori on symptoms of functional dyspepsia is uncertain, and the data in Asian scenario are scanty. The study aimed to see H. pylori positivity rate in patients of functional dyspepsia and the effect of its eradication on symptoms. Methods: Randomized, double-blind, placebo-controlled study was the study design used. Patients of functional dyspepsia defined as per Rome 2 criteria were tested fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 20 publications
3
37
3
1
Order By: Relevance
“…This prevalence was lower compared to similar study in India by Sodhi et al and in China by Xu et al 13,14 The prevalence of H. pylori infection in this study was higher compared to several previous studies in North Sulawesi, Surabaya, and Jakarta which were 14.3%, 11.5%, and 9.5%, respectively. 15,16,17 The demography of population with H. pylori infection in this study was similar to those of several previous studies which stated that low economic status, densely populated area, not clean water, smoking, and alcohol consumption were strongly correlated with the presence of H. pylori infection.…”
Section: Discussioncontrasting
confidence: 75%
“…This prevalence was lower compared to similar study in India by Sodhi et al and in China by Xu et al 13,14 The prevalence of H. pylori infection in this study was higher compared to several previous studies in North Sulawesi, Surabaya, and Jakarta which were 14.3%, 11.5%, and 9.5%, respectively. 15,16,17 The demography of population with H. pylori infection in this study was similar to those of several previous studies which stated that low economic status, densely populated area, not clean water, smoking, and alcohol consumption were strongly correlated with the presence of H. pylori infection.…”
Section: Discussioncontrasting
confidence: 75%
“…In Asia, the studies published over the last year showed high prevalence rates of H. pylori infection ranging from 54% to 76% [10][11][12][13][14][15][16]. Only one study carried out on healthy individuals in Saudi Arabia showed a low prevalence of infection of about 28% [17].…”
Section: Prevalence Of Helicobacter Pylori Infectionmentioning
confidence: 99%
“…(Hanafi and Mohamed, 2013, Ozaydin et al, 2013, Alebie and Kaba 2016. On the other hand, in most studies, there was no significant association between smoking and H. pylori infection (den Hollander et al, 2013, Zhu et al, 2014, Sodhi et al, 2013, Almehdawi, 2016, Almehdawi and Ali, 2016, Camargo et al, 2004.…”
Section: Resultsmentioning
confidence: 99%